Applying the phenotype approach for rosacea to practice and research3. (17th July 2018) - Tan, J.; Berg, M.; Gallo, R.L.; Del Rosso, J.Q.
Summary: Background: Rosacea diagnosis and classification have evolved since the 2002 National Rosacea Society expert panel subtype approach. Several working groups are now aligned to a more patient‐centric phenotype approach, based on an individual's presenting signs and symptoms. However, subtyping is still commonplace across the field and an integrated strategy is required to ensure widespread progression to the phenotype approach. Objectives: To provide practical recommendations that facilitate adoption of a phenotype approach across the rosacea field. Methods: A review of the literature and consolidation of rosacea expert experience. Results: We identify challenges to implementing a phenotype approach in rosacea and offer practical recommendations to overcome them across clinical practice, interventional research, epidemiological research and basic science. Conclusions: These practical recommendations are intended to indicate the next steps in the progression from subtyping to a phenotype approach in rosacea, with the goals of improving our understanding of the disease, facilitating treatment developments and ultimately improving care for patients with rosacea. Abstract : What's already known about this topic? Rosacea diagnosis and classification have evolved from a subtype to a phenotype approach. Adoption of the phenotype approach has begun, but more widespread adoption and support across the field are required to ensure a complete transition. What does this study add? We offer practical guidance for clinical practice, interventional and epidemiological research, and basic science, to help overcome challenges and facilitate comprehensive uptake of the phenotype approach in rosacea Linked Editorial:  Thyssen. B J Dermatol 2018;179 :551–552 . Plain language summary available online Respond to this article